influence of service quality and student perceived value on student satisfaction and competitive advantage in higher education - Sahyar Sahyar (Proceedings of AICS - Social Sciences, 2017)
This research aimed to analyze: the influence of service quality and student perceived value on student satisfaction; the influence of service quality and student perceived value on competitive advantage. Sample in this research were 157 postgraduate students of State University of Medan. Technical sampling used proportional random sampling. Data analyses used multiple regression and path analyses. Statistical test with 0.05 significant values showed: there were positive and significant influence service quality and student perceived value on student satisfaction simultaneously and partially; there were positive and significant influence service quality and student perceived value on competitive advantage simultaneously and partially; The influence of student perceived value predicted student satisfaction or competitive advantage was greater than service quality.